2014
DOI: 10.1002/er.3241
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic hydrogen production from ethanol steam-reforming reaction on NixMoy/SBA-15 catalytic system

Abstract: SUMMARYThis study examined the effects of advanced bimetallic catalytic species of Ni and Mo on hydrogen production from ethanol steam reforming. Ni x Mo y /SBA-15 exhibited significantly higher ethanol steam-reforming activity at mild temperatures than monometallic Ni/SBA-15; the highest activity was achieved using the Ni 0.95 Mo 0.05 /SBA-15 catalyst. H 2 production and ethanol conversion were maximized at 70-87% and 90-92%, respectively, over the temperature range of 500 to 800°C with an EtOH : H 2 O ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
2
11
0
1
Order By: Relevance
“…When the Ni loading further increases to 40%, there is a slight increase of CH 4 yield. In a study of Kim et al, 30% Ni/SBA‐15 catalyst, S/C ratio of 1.5, and 550°C to 800°C temperature range have been employed for ethanol steam reforming, and the corresponding hydrogen yield could reach about 70% at 700°C. Wu et al obtained a maximum hydrogen yield of 72.0% at 20% Ni/SiO 2 catalyst, S/C ratio of 4, and reforming temperature of 600°C from ethanol steam reforming.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the Ni loading further increases to 40%, there is a slight increase of CH 4 yield. In a study of Kim et al, 30% Ni/SBA‐15 catalyst, S/C ratio of 1.5, and 550°C to 800°C temperature range have been employed for ethanol steam reforming, and the corresponding hydrogen yield could reach about 70% at 700°C. Wu et al obtained a maximum hydrogen yield of 72.0% at 20% Ni/SiO 2 catalyst, S/C ratio of 4, and reforming temperature of 600°C from ethanol steam reforming.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, higher activity and lower cost make suitable choice for using the nickel‐based catalysts to produce H 2 through steam reforming process. Many kinds of catalyst supports, ie, SiO 2 , montmorillonite, ZnO, ceramic foam, and SBA‐15 have been investigated for Ni catalytic steam reforming . The characteristics of Ni catalysts are considered to be affected by the chemical composition and the physical structure of catalyst support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the support materials, the most commonly used supports are α‐Al 2 O 3 , γ‐Al 2 O 3 , SiO 2 , MgO, MgAl 2 O 4 , CeO 2 , ZrO 2 , etc. . Surface acid sites presented in the supports may promote carbon formation on the catalyst surface , so that the supports with relatively low concentrations of Lewis acid sites such as MgO, ZrO 2 , and La 2 O 3 can lower the coke deposition rate .…”
Section: Reforming Catalystsmentioning
confidence: 99%
“…The choice of catalyst is the key to improve the conversion of phenols. Ni‐based catalysts are often used for steam reforming due to their strong catalytic activity . However, it has been found that due to the complex composition of phenols, the strong acid sites of Ni‐based catalysts tend to cause large amounts of reactants to adsorb on the surface and coking, which lead to catalyst deactivation.…”
Section: Introductionmentioning
confidence: 99%